Democratic Leadership: Upaya Kepala Sekolah dalam Membangun Kualitas Peserta Didik di Sekolah Dasar (SD) Tunas Teladan Palembang - Kris Setyaningsih (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2019)
This research aims to investigate the leadership style of school principle of Tunas Teladan Elementary School Palembang and its’ implications to the quality of students. Using a descriptive qualitative approach, the data was collected through documentation, interviews, and observation. The study found that: 1) the leadership style of the headmaster in Tunas Teladan Elementary School, Palembang, is democratic combination with family values, but occasionally in certain situations he applies an authoritarian leadership pattern; 2) the leadership style brought about positive implications for the quality of students, both viewed from academic and non-academic aspects. Based on the results of these studies, it is expected that the leadership pattern of the school principals in Tunas Teladan Elementary School Palembang can be learnt as an example model for managers of educational institutions, both formal and non-formal, especially in improving the quality of students.